OPEN BIDDING PHENOMENON JPT PRATAMA POST REGIONAL AUTONOMY - Kamaludin Kamaludin; Rini Indriani (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
The purpose of this study is to capture the phenomenon of the open bidding process carried out in order to select apparatus who have sufficient capacity, competition and integrity to fill certain positions so that they can carry out their tasks more effectively and efficiently. The research design used was a qualitative research design, which investigated the open selection of Echelon III structural officials in the “R” Regency Government Environment (initials in order to maintain the confidentiality of informants) in Bengkulu Province. Research results: (1) The selection of high ranking pratama officials in the Regency District